Direct oral anticoagulants – a new chapter in anticoagulation therapy - Stepanović-Petrović, Radica; Nastić, Katarina (Archives of Pharmacy, 2020)
Thromboembolic events are the leading cause of morbidity and mortality worldwide. From the second half of the 20th century, vitamin K antagonists (VKAs), warfarin and acenocoumarol, were the only anticoagulants taken orally. The major reform in anticoagulation therapy was made by the advent of direct oral anticoagulants (DOACs), about 10 years ago. Direct thrombin inhibitor (dabigatran) and direct inhibitors of factor Xa (rivaroxaban, apixaban, edoxaban, and betrixaban) have demonstrated favorable risk/benefit ratio. Compared to warfarin, DOACs are associated with a predictable pharmacokinetic profile, lower severe bleeding complications, particularly intracranial hemorrhages, and minimal drug interactions. Moreover, DOACs achieve a rapid onset of action and have shown comparable efficacy with warfarin and low molecular weight heparin (LMWH) in clinical trials. As a result, DOACs are now replacing VKAs and LMWH for many indications including stroke and systemic embolism prevention in nonvalvular atrial fibrillation, prevention, and treatment of venous thromboembolism and thromboprophylaxis following total knee/hip replacement surgery. In addition, rivaroxaban (in combination with aspirin alone or aspirin and clopidogrel) is used in the prevention of atherothrombotic events following acute coronary syndrome with elevated cardiac biomarkers. In case of severe bleeding complications under DOACs treatment, antidotes are available; idarucizumab for dabigatran reversal and andexanet alfa for rivaroxaban and apixaban.
Keywords: direct oral anticoagulants; dabigatran; rivaroxaban; apixaban; edoxaban; betrixaban